Characterization of a spontaneous microphthalmia-like mutant mouse with isolated ocular defects - Jianying Wang; Fei Gao; Yuqiang Zheng; Mingqi Zhang; Yuzhu Zhou; Zhuoshi Wang; Jun Li (PLoS ONE, 2026)
Microphthalmia is a significant eye defect owing to its profound effects on visual acuity. Microphthalmia accounts for 3.2%–11.2% of blind children. To date, there has been no cure for this disease. In this study, we aimed to identify microphthalmia-like mutant mouse and study its growth and development. In this study, we identified mutant mice exhibiting eye abnormalities using a forward genetics approach in a C57BL/6J cohort. To identify ocular characteristics of the mutant mouse, we conducted systematic evaluations including basic measurements (body length, body weight, and palpebral fissure width), optical coherence tomography (OCT), optomotor response (OMR), and hematoxylin-eosin (H&E) staining. At early developmental stages, there are notable differences in body length and weight between mutant and normal mice. Mutant mice displayed microphthalmia-like phenotypes, characterized by significantly reduced eyeball and lens sizes as well as decreased anterior chamber depth compared to wild-type controls. Visual impairment was evident in the mutant mice. Mutant mice exhibited rosette-like structures in the retina without impacting other organs of the body. Overall, these results support microphthalmia-like mutant mouse as a valuable tool for studying this congenital ocular malformation.